2018
DOI: 10.1142/s0218196718500443
|View full text |Cite
|
Sign up to set email alerts
|

The equation solvability problem over supernilpotent algebras with Mal’cev term

Abstract: In 2011 Horváth gave a new proof that the equation solvability problem over finite nilpotent groups and rings is in P. In the same paper he asked whether his proof can be lifted to nilpotent algebras in general. We show that this is in fact possible for supernilpotent algebras with a Mal'cev term. However, we also describe a class of nilpotent, but not supernilpotent algebras with Mal'cev term that have coNP-complete identity checking problems and NP-complete equation solvability problems. This proves that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…For CEQV this was observed in [AM10]. For CSAT similar observation was made in [Kom18], [IK18] and [Aic19b], using the fact that every polynomial can be expressed as a 'sum' of absorbing polynomials.…”
Section: Circuit Satisfiability and Equivalencesupporting
confidence: 67%
“…For CEQV this was observed in [AM10]. For CSAT similar observation was made in [Kom18], [IK18] and [Aic19b], using the fact that every polynomial can be expressed as a 'sum' of absorbing polynomials.…”
Section: Circuit Satisfiability and Equivalencesupporting
confidence: 67%
“…In both cases it was shown that considered algorithm works in polynomial time but the degree of the polynomial came from application of Ramsey Theory and was really huge. Later it was independently shown in [24] and [16] that essentially the same algorithm works for supernilpotent algebras from congruence modular variety in polynomial time with the same huge degree of the polynomial. This results was improved by Aichinger in [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several articles considering this new approach to solving equations have appeared e.g. [24], [17], [1], [21], [23], [18]. In this paper we will present the results in terms of Csat, however for clarity we mention, that all the algorithms and upper bounds presented here apply also to the original definition of the problem as polynomials can be represented by circuits expanding size of the representation only by constant factor.…”
Section: Introductionmentioning
confidence: 99%
“…The results in [IK18] link the existence of absorbing polynomials, commutator theoretical properties, and the complexity of CSAT(A) and CEQV(A) for algebras from congruence modular varieties: For so called supernilpotent algebras A, which do not have absorbing polynomials of arbitrary big arities, the problems are in P (for CSAT this was independently shown in [Kom18], and for CEQV already in [AM10]). On the other hand, very roughly speaking, non-nilpotent algebras allow to efficiently construct circuits, which express absorbing polynomials, and therefore (almost always) have hard CSAT and CEQV problems.…”
Section: Introductionmentioning
confidence: 99%